Sedimentologi dan Stratigrafi Fasies Endapan Danau Purba Tondano, Kabupaten Minahasa (Sulawesi Utara) (Berdasarkan pada Analisis Geologi Bawah Permukaan Sehubungan dengan Studi Deformasi Landform) - Herman Mulyana; Santoso Santoso (Jurnal Geologi dan Sumberdaya Mineral, 2006)
The studied area is located in the low-land area of the northern part of Tondano Lake which is dominated by Quaternary lake and fluvial deposits. Based on the sub-surface data, the lithofacies distribution of the deposit can be divided into: (a) pyroclastic deposit, (b) repetition between channel sand lake and lake or swamp deposits and, (c) floodbasin and swamp deposits. The maximum development of the environmental deposition of Tondano Lake is indicated by formation of 1 up to 3 facies, while facies 4 which is situated above them was influenced by decrease of the lake environment. The increasing and decreasing of the lake environment in this area can not be traced continously. It shows a combination of spesific facies arrangement, such as: the lower part, indicated by volcanic activities which were deposited by water; the middle part, indicated by lake invironment; and the upper part, indicated by the end of a volcanic activity which was then followed by the development of a swamp environment and flood basin.Â Keywords: facies, eruption, climate, tectonics